2023
DOI: 10.3390/biomimetics8010033
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Changes in Adipose Tissue in the Newly Formed Bone Induced by Recombinant Human BMP-2 In Vivo

Abstract: Recombinant human bone morphogenetic protein-2 (rhBMP-2) induces osteogenesis and adipogenesis in bone scaffolds. We evaluated rhBMP-2-induced long-term changes in adipose tissue in the newly formed bone in different scaffolds forms. Bovine bone particles and blocks were grafted along with rhBMP-2 in the subperiosteal space of a rat calvarial bone, and the formation of new bone and adipose tissue were evaluated at 6 and 16 weeks after the surgery. The bone mineral density (BMD) and trabecular thickness (TbTh) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Borsani et al [91] found that RSV reversed zoledronate-suppressed human osteoblast differentiation and its associated low BMP2 expression. Notably, BMP-2 is one of the most studied members of the BMP family and has been identified as the most effective inducer of osteogenesis [92].…”
Section: The Effects Of Rsv On Osteoblast-bone Forming Cellsmentioning
confidence: 99%
“…Borsani et al [91] found that RSV reversed zoledronate-suppressed human osteoblast differentiation and its associated low BMP2 expression. Notably, BMP-2 is one of the most studied members of the BMP family and has been identified as the most effective inducer of osteogenesis [92].…”
Section: The Effects Of Rsv On Osteoblast-bone Forming Cellsmentioning
confidence: 99%